The Effect of Learning Supervision, Professional Competency and Pedagogical Competency on Elementary Teacher Performance - Jul Erixon PH Siburian; Arif Rahman; Zulkifli Matondang (RIRAI Publisher, 2024)
This research aims to determine the effect of: (1) learning supervision on pedagogical competence; (2) supervision of learning regarding professional competencies; (3) learning supervision of performance competencies; (4) pedagogical competence on performance; (5) professional competence on performance; (6) supervision of learning towards performance through professional competence; and (7) supervision of learning towards performance through pedagogical competence. This research is quantitative, using the path analysis method. There is a population of 168 elementary school teachers in Tiga Lingga District. Slovin's sample was 116 people. The research hypothesis was tested using simultaneous and partial analyses. The research results show that: (1) there is an influence of learning supervision on professional competence; (2) there is an influence of learning supervision on pedagogical competence; (3) there is an influence of learning supervision on performance; (4) there is an influence of professional competence on performance; (5) there is an influence of pedagogical competence on performance; (6) Learning supervision has a positive effect on teacher performance through professional competence, meaning the contribution of the influence of learning supervision on teacher performance through professional competence. The contribution of the effect of learning supervision on teacher performance through pedagogical competence.